2016
DOI: 10.1177/1521025116669954
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Persistence Outcomes of GEAR UP Students: Leveling the Playing Field in Higher Education

Abstract: Given the major investment in the Gaining Early Awareness and Readiness for Undergraduate Programs (GEAR UP) grant, rising postsecondary access, trends in poor persistence and retention rates, and the ongoing accountability measures in higher education, it is critical to examine factors related to postsecondary performance and persistence of GEAR UP students in comparison to their peers. College performance and persistence of 298 State GEAR UP students were compared with other first-time, first-year students (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
(43 reference statements)
0
5
1
1
Order By: Relevance
“…Knaggs et al (2015) found greater college persistence rates for all GEAR UP students and specifically for low-SES students. In contrast, Sanchez, Lowman, and Hill (2016) observed no significant relationship between GEAR UP participation and subsequent college GPA or retention at a single public research university. For both studies, the singleinstitution sample (of a high school and university, respectively) and the possibility of unobserved differences between GEAR UP and non-GEAR UP students limit the strength and generalizability of the conclusions.…”
Section: Gear Up and College Outcomescontrasting
confidence: 64%
“…Knaggs et al (2015) found greater college persistence rates for all GEAR UP students and specifically for low-SES students. In contrast, Sanchez, Lowman, and Hill (2016) observed no significant relationship between GEAR UP participation and subsequent college GPA or retention at a single public research university. For both studies, the singleinstitution sample (of a high school and university, respectively) and the possibility of unobserved differences between GEAR UP and non-GEAR UP students limit the strength and generalizability of the conclusions.…”
Section: Gear Up and College Outcomescontrasting
confidence: 64%
“…95, 2021 universidad pública que participaron de un programa de preparación temprana para ingresar a la universidad llamado GEAR UP, que, pese a obtener puntajes más bajos en exámenes estandarizados para ingresar a la universidad en Estados Unidos (ACT), tuvieron un rendimiento y persistencia igual al grupo de control compuesto por 1841 estudiantes. Además, este estudio detectó que el GPA junto a los créditos obtenidos podrían ser predictores de persistencia, y que los estudiantes de este programa tenían mayor probabilidad de ser hispanos o latinos y menor probabilidad de ser de áreas urbanas del estado (Sanchez, Lowman y Hill, 2018).…”
Section: Ayudas Financieras E Inclusión: Oportunidades De Estudiantes De Bajos Ingresos Minorías Y En Situación De Discapacidadunclassified
“…Bowman, Kim, Ingleby, Ford, and Sibaouih (2018) found that GEAR UP had a positive effect of three to four percentage points on enrollment, with similar effects across SES and racial groups, while Knaggs et al 2015found a positive effect on enrollment overall and for low-SES students, but not for racial minority students. Effects on persistence are similarly mixed, with studies showing similar rates of persistence compared to non-GEAR UP peers (Bowman et al, 2018;Sanchez, Lowman, & Hill, 2018) or positive effects for low-SES students but not racial minority students (Knaggs et al, 2015). These mixed results illustrate that programs like GEAR UP may be able to reduce some barriers to postsecondary opportunities, but may not be able to address performance differences at the high school and postsecondary levels that stem from accumulated and persistent inequities before and throughout schooling (Author, 2008;Cunha, Heckman, Lochner, & Masterov, 2006;McLoyd, 1998;Noguera, Bishop, Howard, & Johnson, 2019;Reeves & Halikias, 2017;Restuccia & Urrutia, 2004).…”
Section: Initiatives To Promote Postsecondary Enrollmentmentioning
confidence: 99%